I'm going to use the substitution method.
If y = - 3/2 - 7, then:
1/2x + 5 = - 3/2x - 7
Combine like terms:
4/2x = - 12. Mutiply both sides by 2/4 to get x = -12 (2/4)
Simplify to get:
x = - 6.
Plug - 6 back in for x in either equation.
Y = 1/2( - 6) + 5 which becomes Y = - 3 + 5.
X = - 6, Y = 2
It would be called a mess up on ur paper
Answer:
420
Step-by-step explanation:
7 * 3 = 21
21 * 2 = 42
42 * 10 = 420
7 * 3 * 2 * 10 = 420
<u>The area is 420</u>
Answer:
i'm not sure if this is the right answer
51/200
tell me if i'm wrong